Analisis Strategi Pembelajaran PQ4R Untuk Menentukan Ide Pokok Pada Teks Eksplanasi - Romlah Romlah; Muhammad Alfan; Tri Kuncoro (linguistic, literature, and teaching, 2023)
The low learning outcomes of grade 6 students at SDN 3 Dawuhan, especially when learning to determine the main idea of ​​an explanatory text, is caused by several factors, namely internal and external. External factors include variations in the learning model carried out by the teacher which are still not optimal. The subjects of this study were 6th grade students at SDN 3 Dawuhan, consisting of 10 students. This study uses a descriptive qualitative research approach with data collection techniques through tests, observations and interviews. The purpose of this study was to test the effectiveness of the PQ4R learning strategy (Preview, Questions, Read, Reflect, Reside and Review) in learning Indonesian to determine the main idea of ​​an explanatory text. The results obtained are, 1) increasing the ability to ask questions, 2) increasing self-confidence, 3) increasing the ability to think critically and 4) the ability to understand reading. Suggestions for future research, so that there are efforts to cultivate reading activities for students so that they can increase vocabulary treasury which will further improve reading comprehension skills as well. Keywords: Main idea, PQ4R, Explanatory text